PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PEMILIHAN KEAKTIFAN DIVISI DALAM LAPORAN PENGAWASAN BIDANG - Intan Gya Agisti; Lita Karlitasari; Dini Suhartini (Jurnal Teknoinfo, 2025)
Bogor Class IA Religious Court is a government institution responsible for carrying out the mandate of the law based on religious law. Currently the supervision process is still carried out manually, so it takes a long time in terms of supervision and is not monitored in the activeness of each division. Therefore, it is recommended to develop a decision support system for division activeness in field supervision reports by supervisory judges. This system is designed web-based using the Simple Additive Weighting (SAW) method to evaluate division performance scores based on criteria, namely processing time, follow-up, evidence, number of completed tasks and final results. Supervision data is taken from the fourth quarter of 2023. The evaluation results show that the Judicial Administration division is ranked first with the highest score of 0.934, then for rank two is occupied by General Administration with a score of 0.895, for rank three is occupied by Trial Administration with a score of 0.741 and for rank four is occupied by two divisions namely Case Administration and General Services with the same score of 0.247. After that, a system accuracy test was carried out on the SAW algorithm using the Mean Absolute Percentage Error (MAPE) method, which resulted in an average prediction error value of 19.18%, indicating that the ability of the forecasting model was classified as good. The developed system is expected to improve the efficiency and effectiveness of the supervision process at the Bogor Class IA Religious Court.